Effect of physical treatments on germination of Ginkgo biloba L. - Koczka, N.; Orlóczi, L.; Ferenczy, A. Z.; Stefanovits-Bányai, É.; Dimény, J. (International Journal of Horticultural Science, 2000)
In our country the maindenhair tree (Ginkgo biloba L.) is raised mainly from seeds, so the aim of our experiments was to determine the most useful generative propagation method. However, some experiments have been conducted earlier connected to the germination of the species, but the comparative control of physical seed treatment was done first time by the authors.After the statistical evaluation of the results it can be stated that the percentage of germination has significantly increased if the seeds received physical treatment (scalding, mechanical scouring). Hereby the pericarp is getting soft or growing thinner, so the germination of the seed is easier. These treatments are extraordinarily simple, easy to carry out and their effect is very favourable, that is why their use is strongly advised.Comparing the seeds collected at different times was found that the ability of germination is decreasing proportionally with the time spent in the open field. On the basis of our experiments and of earlier practice in Hungarian tree nurseries, our opinion is that the stratification of seeds is not necessary.